Emergency Caesarean Section in a Patient with HELLP Syndrome and Intramural Myoma: A Case Report - Cholili, Muhamad Nofa (Asian Journal of Health Research, 2024)
Introduction: The syndrome of HELLP, often a complication of severe pre-eclampsia, is influenced by factors like multiparity, advanced maternal age, and potential genetic associations. Intramural Myoma have been linked to a 44% increased risk of hypertension in pregnant women, potentially contributing to the initiation and progression of pre-eclampsia, particularly due to their rapid expansion during pregnancy. This study reported a patient with intramural myoma and HELLP Syndrome in 35-36 weeks of gestation age. Case Presentation: A 40-year-old woman in her 35-36 weeks of gestation sought emergency care at General Hospital Dr. Saiful Anwar Malang due to escalating severe headaches. As a third-time expectant mother with a history of five antenatal visits, she presented with elevated blood pressure (219/110 mmHg), a BMI of 32 kg/m2, and various concerning findings, leading to a diagnosis of impending eclampsia, severe preeclampsia (HELLP syndrome), fetal distress, severe hypoalbuminemia, intrauterine growth restriction (IUGR), and other complications. The patient underwent an urgent cesarean section, revealing an intramural uterine myoma, followed by bilateral ligation of uterine arteries to address bleeding and myomectomy. Postoperatively, she received a magnesium sulfate infusion, her blood pressure stabilized at 143/92 mmHg and Hemoglobin 12,40 g/dl. Conclusion: Intramural myoma increases the risk of preeclampsia during pregnancy. Emergency C-section is an effective measure to address complications for both the mother and the baby, and bilateral ligation of uterine arteries can minimize surgical bleeding.